GENE-62. IDENTIFICATION OF FGFR4 p.G388R VARIANT IN CEREBELLAR HEMANGIOBLASTOMAS. (11th November 2019) - Snuderl, Matija; Kannan, Kasthuri; Gagner, Jean-Pierre; Mashiach, Elad; Karajannis, Matthias; Heguy, Adriana; Zagzag, David
Abstract: BACKGROUND: While most hemangioblastomas (~70%) are sporadic and occur predominantly in the cerebellum, they may present as well as familial form associated with von Hippel-Lindau (VHL) syndrome, an autosomal dominant disorder caused by germline mutations of the VHL gene that trigger nuclear translocation of hypoxia-inducible factor (HIF)-1α and angiogenesis. Although inactivation of VHL, a tumor suppressor gene, has been observed in hemangioblastomas, the underlying pathogenic mechanisms responsible for familial and sporadic hemangioblastomas remain incompletely understood. METHODS: Whole exome sequencing of cerebellar hemangioblastoma tumors and matched blood leukocytes from 24 patients, age 24–63, was performed. After preparation and amplification of barcoded libraries, exomes were captured using Kapa Biosystems methodology and paired-end sequenced on Illumina HiSeq 2500 to an average 100-fold coverage. Following read alignment to hg19 genome, tumor and germline (leukocyte) sequences were compared, and pathogenic single nucleotide variants (SNVs) identified and validated by re-sequencing followed by pathway analysis. Additionally, tumor RNA isolated using Maxwell Promega was sequenced on Illumina instrument and the expression counts determined and normalized. RESULTS: We found 314 pathogenic and/or highly deleterious mutations (both germline and somatic) with a median of 13 mutations per patient. Five patients had VHL syndrome (germline VHL mutation) and 4 carried somatic VHL mutations. Among the VHL tumors, 82 mutations were identified, including HNF1B, NOTCH1 and TCF7L1, suggesting a potential contribution of altered RNA metabolism based upon pathway analysis. Among all hemangioblastomas, germline growth factor receptor variants ( FGFR4 p.G388R (14/23 (61%) patients), IGF1R, PDGFRA and TYK2 ) known to activate STAT3 signaling and induce HIF-1α and angiogenesis, were identified. Non-hierarchical clustering of RNA sequencing data revealed two transcriptionally-distinct subtypes of hemangioblastomas. CONCLUSIONS: Our findings indicate that hemangioblastomas can also occur by germline mutations known to activate STAT3 signaling, which may have significant implication in genetic testing and counseling of patients with hemangioblastomas.